PENGARUH SUHU PENGUKUSAN TERHADAP SIFAT FISIKA KIMIA TEPUNG IKAN RUCAH - Sipayung, Mely Y; ', Suparmi; ', Dahlia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis research was aimed to determine the best steamed temperature and to determine the steamed effect on phsycochemical of trash fish. The research was conducted on June-July 2014 in fishery processing laboratory and fishery chemical laboratory Faculty of Fisheries and Marine Science Riau University, and this research was conducted also in food laboratory Bogor Agriculture Institute. Trash fish was obtained from Tanjung Beringin Village, Rampah - North Sumatera. The metode used in this research was completely randomized design (CRD) with 3 treatments of steamed temperature S1 (100 ºC), S2 (90 ºC) and S3 (80 ºC).The results showed that the treatment S3 (80 ºC) of steamed temperature was the best treatment with absorption 126.67, white degree 33.67, pH 6.41 and yield 16.90. Chemical characteristic for ash content 17.72 %, water content 7.51%, protein content 50.95%, fat content 7.70 % and crude fiber 4.22%.Keywords: Trash fish, flour, temperature, steam and physicochemical characteristics